A Fixed Point Approach to the Fuzzy Stability of a Mixed Type Functional Equation (Communications in Mathematical Research, 2021)
Through the paper, a general solution of a mixed type functional equationin fuzzy Banach space is obtained and by using the fixed point method a generalizedHyers-Ulam-Rassias stability of the mixed type functional equation in fuzzy Banachspace is proved.